Can Revenue Recycling Kill Green Technology? - Katinka Holtsmark (CESifo GmbH, 2024)
Carbon tax revenue recycling – returning tax revenue to firms or households that are covered by the carbon tax – can potentially increase political acceptance for carbon taxation and prevent undesirable distributional outcomes and off-shoring. This paper uses a stylized theoretical model to analyze the long-run effects of carbon tax revenue recycling in a sector where there are knowledge spillovers between firms. The paper shows that recycling tax revenue to polluting firms can impede incentives to invest in green technologies and, in some settings, completely curb green investment. This is the case even if the individual transfers are small relative to aggregate government revenues and not contingent on firm-level emissions or investment levels. The disincentive to invest when revenues are recycled arises because a firm investing in green technology may lower not only their own emissions, but also those of other firms, when there are knowledge spillovers between them. When revenues are recycled, the emission reductions from the rest of the industry will lower the transfer received by the investing firm.
Keywords: H23; Q54; Q58; 330; green transition; technological development; carbon tax; revenue recycling